Numerical evaluation of iterative algorithm for plasticity effect correction in residual stress measurements using radial DSPI and the hole-drilling method - Wilvert, Thiago; Viotti, Matias R.; Jr, Armando Albertazzi (Optics and lasers in engineering, 2025)
•Correction of the plasticity effects for residual stress measurements in the Hole-drilling method.•Expansion of the applicability of the optical Hole-drilling technique.•Mapping the inclination of the displacements around the hole.•Optimizing the residual stress measurement by coupling an iterative algorithm with full-field displacement data.•In this article, the applicability of the optical Hole-drilling method is expanded by coupling an iterative algorithm with full-field displacement data to perform the correction of high residual stress measurements. The standard ASTM E837-20 states that considerable deviations are generated when measuring high levels of residual stresses above 80% of the yield stress with the Hole-drilling Method (HDM). The elastic assumption overestimates the stress levels when elastoplastic strains take place during the experimental measurement procedure. Researchers have long highlighted the potential applications of optical techniques to approach the plasticity effects in the HDM, but no information has been found on the subject. This work numerically evaluates an iterative algorithm that enables the measurement of high levels of residual stresses using optical techniques. First, the residual stress measurement is simulated by obtaining the full field data from a finite element model. The elastically evaluated stresses are obtained with the aid of the optical strain gauge formalism. Then, the partial derivative of the radial displacement with respect to the radius as a function of theta is evaluated for a pre-determined annular region around the hole. These values are used as input for the iterative algorithm, which compares it with the ones computed with the elastoplastic model. The existing iterative algorithm was modified to receive and process the available data. In this way, the deviations generated by the plasticity effects are obviated and the final user receives a corrected evaluation for the residual stress measurement. Besides, the access to the strain profiles provides engineers with a better evaluation capacity. The convergence capacity of the iterative algorithm is assessed. This extends the applicability of the optical Hole-drilling technique to measure residual stresses near the yield stress considering the full-field displacement around the hole, accessing it directly until convergence occurs.